Topical Tacrolimus for Lichen Sclerosus: Systematic Review of Efficacy and Safety - Patel, Bhagyshree; Lala, Ayesha; Verdolini, Roberto (Dermatology Practical & Conceptual, 2026)
Introduction: Lichen sclerosus (LS) is a chronic inflammatory dermatosis affecting both genital and extragenital sites, with a prevalence of approximately 3% among females in the United Kingdom, particularly in the post-menopausal population. Although its etiology remains incompletely understood, LS can significantly impair quality of life through pain, pruritus, and scarring [1]. Current guidelines recommend potent topical corticosteroids, most commonly clobetasol, as first-line therapy [2]; however, long-term use is limited by adverse effects such as skin atrophy [3].Objectives: This systematic review evaluates the efficacy and safety of topical tacrolimus in the management of lichen sclerosus.Methods: A comprehensive literature search was conducted in accordance with PRISMA guidelines [4]. Fourteen randomized controlled trials comprising 335 patients with lichen sclerosus were included.Results: Of the included patients, 2% (N=6) presented with extragenital disease and 98% (N=331) with anogenital involvement. Most patients (81%, N=272) were treated with topical tacrolimus 0.1% twice daily, while 19% (N=63) received clobetasol as a comparator. Clinical improvement, ranging from partial symptom relief to complete remission, was observed in 90% (N=244) of tacrolimus-treated patients. Severe adverse events requiring discontinuation were rare (1%, N=3). Compared with corticosteroids, tacrolimus was associated with superior patient-reported outcomes, clinician-reported improvement, and histological response.Conclusion: Topical tacrolimus appears to be a safe and effective therapeutic option for lichen sclerosus, demonstrating favorable clinical and histological outcomes with minimal adverse effects. Further long-term prospective trials are needed to confirm its comparative efficacy, safety, and role in future treatment guidelines.